Return of State Losses In The Investigation Process That Can Eliminate Criminal Perpetrators of Corruption - Andi Mirzan Doda; Fence M. Wantu; Dian Ekawaty Ismail (Universitas Negeri Gorontalo, 2023)
The purpose of writing to be achieved in this paper is to know and analyze the return of state losses in the investigation process that can eliminate criminal perpetrators of corruption. This research is a normative legal research using the statutory approach